1988
DOI: 10.1111/j.1365-2036.1988.tb00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Enprostil, a prostaglandin E2 analogue, in the treatment of duodenal ulcer; a multicentre' comparison with cimetidine

Abstract: In a multicentre trial, 120 patients with endoscopically diagnosed duodenal ulcer were randomly allocated to treatment with either 35 pg enprostil b.d. or 400 mg cimetidine b.d. for up to 6 weeks on a doubleblind basis. After 6 weeks, 82% (42/51) of enprostil-treated patients and 92 % (44/48) of cimetidine-treated patients were healed. Corresponding healing figures on an intention-to-treat basis were 70% and 76%. No significant dfierences were detected between treatments with respect to healing rates or sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Enprostil is a synthetic E 2 dehydro‐prostaglandin withgastric antisecretory and cytoprotective activity 1‐4 . Early clinical studies indicated that enprostil can heal both gastric and duodenal ulcers, with minimal adverse effects, within four to six weeks of the initiation of treatment 5‐9 .…”
Section: Introductionmentioning
confidence: 99%
“…Enprostil is a synthetic E 2 dehydro‐prostaglandin withgastric antisecretory and cytoprotective activity 1‐4 . Early clinical studies indicated that enprostil can heal both gastric and duodenal ulcers, with minimal adverse effects, within four to six weeks of the initiation of treatment 5‐9 .…”
Section: Introductionmentioning
confidence: 99%